2013
DOI: 10.4172/2155-9562.1000150
|View full text |Cite
|
Sign up to set email alerts
|

Are Periventricular Lesions Specific for Multiple Sclerosis?

Abstract: Background The presence of periventricular lesions (PVL) on MRI scans is part of the revised McDonald multiple sclerosis (MS) diagnostic criteria. However, PVL can be found in other neurological diseases including stroke and migraine. Migraine is highly prevalent in patients with MS. Objective To determine if PVL are specific for patients with MS compared to stroke and migraine. Methods We studied patients diagnosed with clinically isolated syndrome (CIS), relapsing-remitting MS (RRMS), migraine, and ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Lastly, the periventricular region was the highest anatomical location of IRLs presence while the cortical was the least. This is to be expected as MS lesions are commonly seen around the ventricles [ 66 ]. Although the focus of this review was mainly in the brain, IRLs were also found in the spinal cord [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the periventricular region was the highest anatomical location of IRLs presence while the cortical was the least. This is to be expected as MS lesions are commonly seen around the ventricles [ 66 ]. Although the focus of this review was mainly in the brain, IRLs were also found in the spinal cord [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its large size, the detection of such lesions is easy, and it may have different shapes with high contrast on edema. FLAIR provides high sensitivity to detect such lesions because it can differentiate the signal from CSF [32] [33]. Juxtacortical lesions are small with a spherical or elliptical shape and have low contrast.…”
Section: Ms Lesions Localizationmentioning
confidence: 99%